Model-Based Software Testing and Analysis with C# - Jacky, Jonathan (Cambridge University Press, 2013)
This book teaches newmethods for specifying, analyzing, and testing software. They are examples of model-based analysis and model-based testing, which use a model that describes how the program is supposed to behave. The methods provide novel solutions to the problems of expressing and analyzing specifications and designs, generating test cases, and checking the results of test runs. The methods increase the automation in each of these activities, so they can be more timely, more thorough, and (we expect) more effective. The methods integrate concepts that have been investigated in academic and industrial research laboratories for many years and apply them on an industrial scale to commercial software development. Particular attention has been devoted to making these methods acceptable to working software developers. They are based on a familiar programming language, are supported by a well-engineered technology, and have a gentle learning curve.